2016
DOI: 10.1097/prs.0000000000002365
|View full text |Cite
|
Sign up to set email alerts
|

One versus Two Venous Anastomoses in Anterolateral Thigh Flap Reconstruction after Oral Cancer Ablation

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 20 publications
1
26
1
Order By: Relevance
“…Lee et al claimed that two vein anastomoses achieved better outcomes with the anterolateral thigh flap, which is one of the workhorse flaps for head and neck reconstruction. 18 Conversely, Khaja et al proved that two vein anastomoses in head and neck free flap did not reduce flap failure rate or postoperative venous thrombosis. 19 In this study, the number of recipient veins did not have any impact on the speech outcome after tongue reconstruction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lee et al claimed that two vein anastomoses achieved better outcomes with the anterolateral thigh flap, which is one of the workhorse flaps for head and neck reconstruction. 18 Conversely, Khaja et al proved that two vein anastomoses in head and neck free flap did not reduce flap failure rate or postoperative venous thrombosis. 19 In this study, the number of recipient veins did not have any impact on the speech outcome after tongue reconstruction.…”
Section: Discussionmentioning
confidence: 98%
“…Many microsurgeons recommend double venous anastomosis if possible because it is considered to reduce flap failure, venous thrombosis, and the need for revision. 17,18 This debate is in progress in the field of head and neck reconstruction as well. Lee et al claimed that two vein anastomoses achieved better outcomes with the anterolateral thigh flap, which is one of the workhorse flaps for head and neck reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…20 For more than 20 years, it has been debated whether to use one or two venous anastomoses. 13,21 The meta-analysis of Riot et al and Ahmadi et al, examining more than 3,000 free tissue transfers, concluded that two venous anastomoses may significantly reduce occurrence of microsurgical venous thrombosis, need for surgical revision, and overall flap Abbreviations: ALT, anterolateral thigh; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…There are flaps with a single venous system (venae comitantes), such as the ALT, groin, and gracilis muscle flaps, and then there exist flaps with dual venous systems (venae comitantes and superficial veins), such as the deep inferior epigastric perforator or the radial forearm flap, for instance. 21 Khashaba and McGregor demonstrated that in cases of a dual venous system, both systems are equally able to drain the flap, which explains why only one anastomosis is sufficient in the majority of cases. 29 Less information is available regarding hemodynamic flow patterns of single venous systems flaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation